The Effect Of Audit Solvency And Opinion On Audit Delay (Empire Study On Technology Companies Listed On The Indonesia Stock Exchange Period 2016 – 2020) - Ayi Srie Yuniawati; Tisna Permana (Journal of Business, Accounting and Finance, 2023)
This study aims to analyze how the effect of Solvency and Audit Opinion either partially or simultaneously on Audit Delay. The population in this study were technology companies listed on the Indonesia Stock Exchange in the 2016-2020 period, using a purposive sampling technique, the samples in this study were 7 companies that were the object of research with 35 units of analysis. The data used is secondary data that comes from the company's financial statements. The analysis technique used is descriptive statistics, classical assumption test, and multiple linear regression. The results show that the relationship between Solvency (X1) and Audit Opinion (X2) is 0.305 in a negative direction. Solvency partially has a significant effect on audit delay in technology companies listed on the Indonesia Stock Exchange for the 2016- 2020 period. This is evidenced by the value of tcount (2.783) which is greater than ttable (2.037) and the value of sig. 0.009 is smaller than the value of 0.05. Audit opinion partially has a significant effect on audit delay in technology companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This is evidenced by the value of tcount (2.073) which is greater than ttable (2.037) and the value of sig. 0.046 is smaller than the value of 0.05. Solvency and Audit Opinion simultaneously affect audit delay in technology companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This is proven by the value of Fcount (4.699) with a probability of 0.016. Because Fcount (4.699) is greater than Ftable (3.285) and the value of sig. 0.016 is less than 0.05.